Interventional Optical Imaging-Monitored Synergistic Effect of Radio-Frequency Hyperthermia and Oncolytic Immunotherapy - Zheng, Hui; Zhang, Feng; Monsky, Wayne; Ji, Hongxiu; Yang, Weizhu; Yang, Xiaoming (Frontiers in Oncology, 2022)
Purpose: To develop a new interventional oncology technique using indocyanine green (ICG)-based interventional optical imaging (OI) to monitor the synergistic effect of radiofrequency hyperthermia (RFH)-enhanced oncolytic immunotherapy. Materials and Methods: This study included (1) optimization of ICG dose and detection time-window for intracellular uptake by VX2 tumor cells; (2) in-vitro confirmation of capability of using ICG-based OI to assess efficacy of RFH-enhanced oncolytic therapy (LTX-401) for VX2 cells; and (3) in-vivo validation of the interventional OI-monitored, intratumoral RFH-enhanced oncolytic immunotherapy using rabbit models with orthotopic liver VX2 tumors. Both in-vitro and in-vivo experiments were divided into four study groups (n=6/group) with different treatments: (1) combination therapy of RFH+LTX-401; (2) RFH alone at 42°C for 30 min; (3) oncolytic therapy with LTX-401; and (4) control with saline. For in-vivo validation, orthotopic hepatic VX2 tumors were treated using a new multi-functional perfusion-thermal radiofrequency ablation electrode, which enabled simultaneous delivery of both LTX-401 and RFH within the tumor and at the tumor margins. Results: In in-vitro experiments, taking up of ICG by VX2 cells was linearly increased from 0 μg/mL to 100 μg/mL, while ICG-signal intensity (SI) reached the peak at 24 hours. MTS assay and apoptosis analysis demonstrated the lowest cell viability and highest apoptosis in combination therapy, compared to three monotherapies (P<0.005). In in-vivo experiments, ultrasound imaging detected the smallest relative tumor volume for the combination therapy, compared to other monotherapies (P<0.005). In both in-vitro and in-vivo experiments, ICG-based interventional optical imaging detected a significantly decreased SI in combination therapy (P<0.005), which was confirmed by the “gold standard” optical/X-ray imaging (P<0.05). Pathologic/laboratory examinations further confirmed the significantly decreased cell proliferation with Ki-67 staining, significantly increased apoptotic index with TUNEL assay, and significantly increased quantities of CD8 and CD80 positive cells with immunostaining in the combination therapy group, compared to other three control groups (P<0.005). Conclusions: We present a new interventional oncology technique, interventional optical imaging-monitored RFH-enhanced oncolytic immunotherapy, which may open new avenues to effectively manage those patients with larger, irregular and unresectable malignancies, not only in liver but also the possibility in other organs.